Conical Diffraction: Conical Diffraction from Approximate Dirac Cone States in a Superhoneycomb Lattice (Ann. Phys. 11/2019). Issue 11 (11th November 2019) - Kang, Yongfeng; Zhong, Hua; Belić, Milivoj R.; Tian, Yiqing; Jin, Kaichao; Zhang, Yanpeng; Li, Fuli; Zhang, Yiqi
Abstract : In article number 1900295, Yiqi Zhang and co‐workers investigate conical diffraction in the superhoneycomb lattice, based on the continuous model. To excite Dirac cone states, the lattice is cut along short‐bearded boundaries and the states close to the Dirac points are obtained, which are called the approximated Dirac cone states. Conical diffraction due to both pseudospin‐1/2 and pseudospin‐1 Dirac cones is displayed graphically and discussed theoretically. The avenue to observe conical diffraction developed here avoids mathematical complexity and is quite direct.